PENERAPAN MODEL PERILAKU PERAWAT TENTANG HAND HYGIENE BERBASIS TEORY OF PLANNED BEHAVIOUR DAN KEPATUHAN PERAWAT MELAKUKAN HAND HYGIENE 5 MOMENT 6 LANGKAH - Apriyani Puji Hastuti; Heny Nurmayunita (Institut Teknologi, Sains, dan Kesehatan RS dr. Soepraoen Malang, 2018)
Introductions: Hand washing is a way to prevent disease and is a process that mechanically removes impurities from the skin of the hands using a handrub. Hand washing has been regarded as one of the most important measures to reduce transmission of microorganisms and prevent infection for more than 150 years. In 2009 the WHO formulated a strategy for implementing 5 6-step moments for health workers. The hand washing procedure is performed before contact with the patient, before performing aseptic procedures, after exposure to fluid, after contact with the patient, after contact with the environment (Ernawati, 2014). Hand-washing behavior of nurses is one of the factors that have a major influence in preventing the occurrence of nosocomial infections. Previous research from Fatmawati, found the number of nurses who perform handwashing procedures 5 moments 6 steps there are in accordance with the stage, and some are not in accordance with the stages that have been set. It was found that more than 20% of nurses on duty only did hand washing after taking action to the patient and did not wash their hands before contact with the patient. Method: The design of this study used pre experimental design with one shot case study approach. Data analysis in this research use with univariate analysis. Result : Compliance nurse about hand washing 5 moments 6 steps of high compliance as much as 335 times the action (70%) and low compliance as much as 65 times the action (14%). While for 5 moments most have low compliance as much as 289 times action (61%) and a small part 86 times action (18%). The nurse performs hand wash in step 1 as much as 439 (99,7%), step 2 count 413 (93,86%), step 3 counted 421 (95,68%), step 4 342 (77,3%), 5 as many as 335 (76.14%) and step 6 of 335 (76.14%). The nurse performs handwashing at moment 1 of 78 (18%), moment 2 is 61 (14%), moment 3 is 276 (73%), moment 4 and moment 5 are 440 (100%).